Pelatihan Pemilahan Sampah pada Anak Sekolah Minggu Jemaat GMIM Maranatha Karame: Training Program on Waste Sorting for Sunday School Children of GMIM Maranatha Karame (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
The formation of new behavioral patterns can be facilitated by the establishment of habits that are initiated during early childhood. The acquisition of knowledge during childhood (5 – 12 years) represents a crucial phase for the formation of healthy and hygienic habits. This occurs through the provision of instructive examples, which facilitate the development of positive behaviors. The objective of this activity was to introduce and familiarize sunday school children with clean and healthy living behaviors through waste sorting training at GMIM Maranatha Karame, Kecamatan Singkil, Kota Manado. This activity employs the use of storytelling as a pedagogical approach. Initially, an animated video is utilized to educate children on the importance of proper waste disposal, emphasizing the necessity for sorting waste at home before its ultimate disposal. This is followed by a question-and-answer session, where children are prompted to reflect on their daily behaviors and attitudes towards waste management and maintaining a clean environment. The evaluation results demonstrate that 98% of children can engage in waste sorting prior to its disposal.